The Synergistic Cytotoxic and Apoptotic Effect of Resveratrol and Naringenin on Y79 Retinoblastoma Cell Line - Rakhshan, Rasul; Atashi, Hesam A.; Hoseinian, Mohammad; Jafari, Aryan; Haghighi, Amirparsa; Ziyadloo, Fatemeh; Razizadeh, Nasim; Ghasemian, Haniyeh; Nia, Mohammad M.K.; Sefidi, Anita B.; Arani, Hamid Z. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Resveratrol is a phenolic natural product, which is found in red grapes and in Japanese knotweed root (Polygonum cuspidatum). Naringenin is one of the flavonoid compounds found in landing grape and other citrus fruits. Both agents exert antioxidant and anti-inflammatory properties. Objective: In this study, the effect of Resveratrol and Naringenin in an in vitro model of retinoblastoma of the eye has been investigated. Methods: XTT and trypan blue assays were used to evaluate the anti-proliferative/cytotixic effect of resveratrol and naringenin in Y79 cells. With the aid of AnnexinV/PI flow cytometry, the kind of cell death was investigated. To assess important gene expression levels at mRNA level involved in apoptosis, Real-time PCR was utilized. Results: Naringenin and resveratrol significantly decreased proliferation and stimulated cell death (mostly apoptosis) in Y79 cells at 50 and 100 (μg/ml) after 24 and 48 hours. Additional cytotoxic effect was observed after 48 hours. Furthermore expression level of Bax and Bcl2 mRNAs altered significantly in all samples treated with 50 (μg/ml) of naringenin, resveratrol, or simultaneously with both. P21 mRNAs expression altered in all mentioned samples except those treated with 50 (μg/ml) of resveratrol. Conclusion: Based on the results, it can be concluded that resveratrol and naringenin can decrease cell viability in retinoblastoma cells in an in vitro dose/time-dependent manner. Albeit more studies are needed to shed the light on the mechanism of action, our data reveal a potential synergistic cytotoxic effect of naringenin and resveratrol on Y79 cells in 48 hours.
Keywords: retinoblastoma